The case for price stability - Goodfriend, Marvin; King, Robert G. (NBER working paper series, 2001)
Reasoning within the New Neoclassical Synthesis (NNS) we previously recommended that price stability should be the primary objective of monetary policy. We called this a neutral policy because it keeps output at its potential, defined as the outcome of an imperfectly competitive real business cycle model with a constant markup of price over marginal cost. We explore the foundations of neutral policy more fully in this paper. Using the principles of public finance, we derive conditions under which markup constancy is optimal monetary policy. Price stability as the primary policy objective has been criticized on a number of grounds which we evaluate in this paper. We show that observed inflation persistence in U.S. time series is consistent with the absence of structural inflation stickiness as is the case in the benchmark NNS economy. We consider reasons why monetary policy might depart from markup constancy and price stability, but we argue that optimal departures are likely to be minor. Finally, we argue that the presence of nominal wage stickiness in labor markets does not undermine the case for neutral policy and price stability.